Periculosidade e loucura no sistema penal: a percepção dos juízes acerca da periculosidade a partir da analise de sentenças de medida de segurança no estado de Mato Grosso - LOURENÇO, Renata (Universidade Federal do Pará, 2017)
This study sought to understand the perception of the concept of dangerousness and persistence of the concept of dangerousness presumption associated with madness in implementing decisions of the security measures from legal discourse emanating from the issued sentences by judges, in order to be the dangerousness the fundamental requirement for the application of this legal instrument. Through the historical context was possible to understand that the concept of dangerousness since its formulation in criminology, under the positive school of law was incorporated by criminal law as legitimizing basis of punitive practices and public security policies with the reasoning of the thesis of the previous defense of society. Punitive processes will delineating to meet the interests of certain social groups involved in each historical period, focusing on specific groups, and in this context has established the concept of madness violence binomial such ingrained currently up in our society. sentences and psychiatric reports processes in compliance with security measures were analyzed in the regions of Cáceres, Cuiabá and Lowland Grande, a total of 36 cases examined. The process analysis is focused on the study of the initial sentences of application of custodial security measures and progression to the outpatient and psychiatric reports that support decisions of application security measure judges. From the construction of the theoretical framework and analysis of sentences was concluded that the issue of dangerousness, although it is at first glance relegated to the legal universe, is not limited to this, since it presents as a key element in the social organization, in the grounds of the thesis defense of society and the legitimacy of punitive state and political and economic order established.